CMZ Reversed Chronic Ethanol-Induced Disturbance of PPAR-α Possibly by Suppressing Oxidative Stress and PGC-1α Acetylation, and Activating the MAPK and GSK3β Pathway - Zeng, Tao; Zhang, Cui-Li; Song, Fu-Yong; Zhao, Xiu-Lan; Xie, Ke-Qin (PLOS ONE, 2014)
Background Cytochrome P4502E1 (CYP2E1) has been suggested to play critical roles in the pathogenesis of alcoholic fatty liver (AFL), but the underlying mechanisms remains unclear. The current study was designed to evaluate whether CYP2E1 suppression by chlormethiazole (CMZ) could suppress AFL in mice, and to explore the underlying mechanisms. Methods Mice were treated with or without CMZ (50 mg/kg bw, i.p.) and subjected to liquid diet with or without ethanol (5%, w/v) for 4 weeks. Biochemical parameters were measured using commercial kits. The protein and mRNA levels were detected by western blot and qPCR, respectively. Histopathology and immunohistochemical assay were performed with routine methods. Results CYP2E1 inhibition by CMZ completely blocked AFL in mice, shown as the decline of the hepatic and serum triglyceride levels, and the fewer fat droplets in the liver sections. Chronic ethanol exposure led to significant decrease of the mRNA and protein levels of peroxisome proliferator-activated receptor α (PPAR-α), which was blocked by CMZ co-treatment. CMZ co-treatment suppressed ethanol-induced oxidative stress, overproduction of tumor necrosis α (TNF-α), and decrease of protein levels of the PPAR-α co-activators including p300 and deacetylated PGC1-α. Furthermore, CMZ co-treatment led to the activation of AMP-activated protein kinase (AMPK), mitogen-activated protein kinase (MAPK), and PI3K/Akt/GSK3β pathway. However, chronic ethanol-induced decline of acyl-CoA carboxylase (ACC) and fatty acid synthase (FAS) protein levels was partially restored by CMZ, while the activation of autophagy appeared to be suppressed by CMZ. Conclusion These results suggested that CMZ suppressed chronic ethanol-induced oxidative stress, TNF-α overproduction, decline of p300 protein level and deacetylation of PGC1-α, and activated AMPK, MAPK, and PI3K/Akt/GSK3β pathway, which might contribute to the activation of PPAR-α and account for the protection of CMZ against AFL.